Analisis Optimasi Pemanfaatan Melati Gambir (Jasminum grandiflorum L.) di Kecamatan Rakit Kabupaten Banjarnegara - Cahyati, Wahyu Nilam; Rahayu, Enni Suwarsi (Universitas Negeri Semarang, 2020)
Melati gambir is a commodity of the floriculture sub-sector of Banjarnegara Regency which is only cultivated in Rakit District. In the range of 2012-2017 the population declined, the lower the interest. The purpose of this research is to analyze efforts to optimize the use of melati gambir through the approval of traditional knowledge of the use of melati gambir; comparing it between gender and age; while analyzing factual use. The research was conducted in five villages in Rakit District in March 2018 and August 2019. Data were collected through semi-structured interviews, questionnaires and direct observation, then analyzed with nonparametric tests. The results showed that traditional knowledge about melati gambir was included in the high category with an average score (94%); The level of knowledge of the elderly is higher than that of adults and adolescents. In contrast, there is no difference in the level of knowledge between men and women; melati gambir by the community is low. The most widely used plant organs are flowers (70%). The community only uses 15.79% of the potential benefits that need to be done to optimize the use of melati gambir. Efforts that need to be done are 1) involving universities or research institutions to assess the potential benefits, 2) collaboration with the Banjarnegara Agriculture Office, investors, entrepreneurs and melati gambir traders associations for product development 3, socialization of utilization melati gambir in order to increase interest in melati gambir cultivation with involving government / private institutions Melati gambir merupakan komoditas sub-sektor florikultura Kabupaten Banjarnegara yang hanya dibudidayakan di Kecamatan Rakit. Dalam rentang tahun 2012-2017 populasinya semakin menurun disebabkan rendahnya minat budidaya akibat pemanfaatan yang kurang optimal. Tujuan penelitian ini adalah menganalisis usaha untuk mengoptimalkan pemanfaatan melati gambir melalui identifikasi pengetahuan tradisional pemanfaatan melati gambir; membandingkannya antar gender dan umur; serta menganalisis pemanfaatan faktual. Penelitian dilakukan di lima desa di Kec. Rakit pada Maret 2018 dan Agustus 2019. Data dikumpulkan melalui wawancara semi terstruktur, angket dan observasi langsung, kemudian dianalisis dengan uji nonparametrik. Hasil penelitian menunjukkan pengetahuan tradisional tentang melati gambir termasuk kategori tinggi dengan rerata skor (94%); Tingkat pengetahuan umur lansia lebih tinggi dibanding umur dewasa dan remaja. Sebaliknya, tidak ada perbedaan tingkat pengetahuan antara laki-laki dan perempuan; Tingkat pemanfaatan secara faktual melati gambir oleh masyarakat tergolong rendah. Organ tanaman yang paling banyak dimanfaatkan adalah bunga (70%). Masyarakat hanya memanfaatkan 15,79% dari potensi manfaat sehingga perlu dilakukan upaya optimasi pemanfaatan melati gambir. Upaya yang perlu dilakukan adalah 1) melibatkan perguruan tinggi atau lembaga penelitian untuk mengkaji potensi manfaat, 2) kerjasama dengan Dinas Pertanian Banjarnegara, investor, usahawan dan asosiasi pedagang melati gambir untuk pengembangan produk serta 3) sosialisasi pemanfaatan melati gambir kepada seluruh lapisan masyarakat di Kecamatan Rakit guna meningkatkan minat budidaya melati gambir dengan melibatkan pemerintah/lembaga swasta.